IR-780 Dye-based Targeting of Cancer-associated Fibroblasts Improves Cancer Immunotherapy by Increasing Intra-tumoral T Lymphocytes Infiltration - Yang, Wei; Chen, Zelin; Qu, Langfan; Zhang, Can; Chen, Hongdan; Zheng, Jiancheng; Chen, Wanchao; Tan, Xu; Shi, Chunmeng (Current Cancer Drug Targets, 2024)
Background: Immune-checkpoint inhibitors (ICIs) against programmed death (PD)-1/PD-L1 pathway immunotherapy have been demonstrated to be effective in only a subset of patients with cancer, while the rest may exhibit low response or may develop drug resistance after initially responding. Previous studies have indicated that extensive collagen-rich stroma secreted by cancer-associated fibroblasts (CAFs) within the tumor microenvironment is one of the key obstructions of the immunotherapy for some tumors by decreasing the infiltrating cytotoxic T cells. However, there is still a lack of effective therapeutic strategies to control the extracellular matrix by targeting CAFs. Methods: The enhanced uptake of IR-780 by CAFs was assessed by using in vivo or ex vivo nearinfrared fluorescence imaging, confocal NIR fluorescent imaging, and CAFs isolation testing. The fibrotic phenotype down-regulation effects and in vitro CAFs killing effect of IR-780 were tested by qPCR, western blot, and flow cytometry. The in vivo therapeutic enhancement of anti-PD-L1 by IR-780 was evaluated on EMT6 and MC38 subcutaneous xenograft mice models. Results: IR-780 has been demonstrated to be preferentially taken up by CAFs and accumulate in the mitochondria. Further results identified low-dose IR-780 to downregulate the fibrotic phenotype, while high-dose IR-780 could directly kill both CAFs and EMT6 cells in vitro. Moreover, IR-780 significantly inhibited extracellular matrix (ECM) protein deposition in the peri-tumoral stroma on subcutaneous EMT6 and MC38 xenografts, which increased the proportion of tumor-infiltrating lymphocytes (TILs) in the deep tumor and further promoted anti-PD-L1 therapeutic efficacy. Conclusion: This work provides a unique strategy for the inhibition of ECM protein deposition in the tumor microenvironment by targeted regulating of CAFs, which destroys the T cell barrier and further promotes tumor response to PD-L1 monoclonal antibody. IR-780 has been proposed as a potential therapeutic small-molecule adjuvant to promote the effect of immunotherapy.
Keywords: anti-PD-L1